A review of catchment-scale water quality and erosion models and a synthesis of future prospects. (April 2019) - Fu, Baihua; Merritt, Wendy S.; Croke, Barry F.W.; Weber, Tony R.; Jakeman, Anthony J.
Abstract: Catchment-scale water quality models have become important tools for water quality management, planning and reporting worldwide. In this review, we synthesise recent developments in water quality modelling, focusing on catchment-scale models of freshwater, non-urban systems and their ability to support catchment management. We explore 10 key attributes in selected existing water quality models. These attributes can be characterised as: model use (model purposes, representation of constituents, scenario analysis, and documentation), model development (process representation, spatial heterogeneities, temporal dynamics, and data requirements), and model performance (calibration, validation and uncertainty tools). We deliberate on 11 key challenges and/or emerging topics in catchment water quality modelling: large-scale applications, model integration, model usability and communication, preliminary data analysis, modelling management practices, technology advancement, incorporating soft data, model identifiability, uncertainty analysis, good modelling practices and capacity building, and differentiating the effects of climate impacts from those associated with land use and management practices. Highlights: The review focuses on the ability of models to support catchment management. Key attributes of model use, development and performance were explored. We discussed 11 challenges and emerging topics for future development. Uncertainty can be reduced through using soft data and optimal monitoring design. A major challenge is separating impacts of climate from land use and management.